2020
DOI: 10.32598/ptj.10.4.348.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Changing Footstrike Pattern on the Amplitude and Frequency Spectrum of Ground Reaction Forces During Running in Individuals With Pronated Feet

Abstract: Purpose: The current study aimed to evaluate the effects of barefoot and shod running with two different styles on ground reaction force-frequency content in recreational runners with low arched feet. Methods: The statistical sample of this research was 13 males with Pronated Feet (PF) (Mean±SD age: 26.2±2.8 y; height: 176.1±8.4 cm; weight: 78.3±14.3 kg). A force plate (Bertec, USA) with a sample rate of 1000 Hz was used to record the reaction forces under each foot. Three test conditions in our study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Therefore, in addition to the changes in the standing position, the abnormalities of this part also affect the movement [7]. Overpronation of the foot is considered a major contributing factor in lower limb injuries [16]. It has been reported that between 0.6% and 8.5% of male players experience an injury to a ligament called the anterior cruciate ligament each year [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in addition to the changes in the standing position, the abnormalities of this part also affect the movement [7]. Overpronation of the foot is considered a major contributing factor in lower limb injuries [16]. It has been reported that between 0.6% and 8.5% of male players experience an injury to a ligament called the anterior cruciate ligament each year [9].…”
Section: Introductionmentioning
confidence: 99%
“…Knee injuries account for approximately 61% of sports injuries [17]. The pronation of the foot and internal rotation of the tibia are coupled with each other and create torsional forces [16]. This torsional stress may lead to ligament tears or dislocation-induced fractures [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation